The Influence of the Project Based Learning Model on Learning Outcomes PPKN On Fourth Grade Students - Anggun Anugrah Manurung; Eva Pasaribu; D. Yuliana Sinaga (PT. Padang Tekno Corp, 2025)
This research aim For knowThe Influence of the Project Based Learning Model on Learning Outcomes PPKN On Students of Class IV of UPTD SD Negeri 122350 Pematangsiantar.Research design implementedis Pre-Experimental Designs method is appropriate with limitations amount samples to be researched.This research will was held at the UPTD of State Elementary School 122350 Pematangsiantar.The time study implemented in the even semester May of the Year Academic Year 2023/2024. Based on results research and discussion that has been put forward can taken conclusion that from pretest results,obtained the average value is 46.35 which is classified as in category low.While average value of results Study posttest students, namely 85.52, which indicates that results after given treatment increase with such a range big.From the average pretest and posttest scores there are difference of 39.17 and based on hypothesis test results with level significant = 0.05 and ttable of 2.034, thitung of 14.737. With thus thitung> ttable 14.737> 2.034, then can concluded that there is the influence of the Project Based Learning Model on results learning PPKN for students Class IV of UPTD SD Negeri 122350 Pematangsiantar.Maka based on Hypothesis Test Results is rejected and accepted which indicates that existence the influence of the Project Based Learning Model is significant to results learning PPKN for students Class IV of UPTD SD Negeri 122350 Pematangsiantar.